Impact of COVID-19 on health-related quality of life in patients with cardiovascular disease: a multi-ethnic Asian study - Lim, Shir Lynn; Woo, Kai Lee; Lim, Eleanor; Ng, Faclin; Chan, Mark Y.; Gandhi, Mihir (Health and quality of life outcomes, 2020)
Background Little is known about the impact of the global coronavirus disease-2019 (COVID-19) pandemic on patients with cardiovascular disease (CVD), the biggest global killer and major risk factor for severe COVID-19 infections. We aim to explore the indirect consequences of COVID-19 on health-related quality of life (HRQoL) of patients with CVD. Methods Eighty-one adult outpatients with CVD were assessed using the EQ-5D, a generic health status instrument with five dimensions (mobility, self-care, usual activities, pain/discomfort, anxiety/depression), before and during the pandemic. Changes in the EQ-5D dimensional responses were compared categorically as well as using the dimension-specific sum-score (range 1–3, with a higher score indicating worse health). The responses and sum-score were compared using the exact test of symmetry and the paired t -test, respectively. Results These patients [mean age (SD) 59.8 (10.5); 92.6% males; 56% New York Heart Association (NYHA) functional class I] had coronary artery disease (69%), heart failure (28%), or arrhythmias (15%). None experienced change in NYHA class between assessments. About 30% and 38% of patients reported problems with at least one of the EQ-5D dimensions pre-pandemic and during the pandemic, respectively. The highest increase in health problems was reported for anxiety/depression (12.5% pre-pandemic vs 23.5% during pandemic; p = 0.035) with mean domain-specific score from 1.12 (SD 0.33) to 1.25 (SD 0.46) (standardized effect size = 0.373, p = 0.012). There was no meaningful change in other dimensions as well as overall HRQoL. Conclusion The COVID-19 pandemic is associated with a significant worsening of the mental health of patients with CVD.